KAJIAN PEMBERIAN BEBERAPA KONSENTRASI AIR LAUT TERHADAP PERTUMBUHAN VEGETATIF BAWANG MERAH - Dewi, Suprayanti Martia; Kisman, Kisman; Nimatullah, Aluh; Nufus, Nofita Hidayatun; Jufri, Afifah Farida (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
Sea water can be an alternative source of nutrition for plants. This research aims to obtain the best application concentration of sea water as a source of micro mineral nutrients for the growth of shallot plants. This research was carried out in Loang Baloq, Mataram, West Nusa Tenggara from June 2023 to August 2023. The experiment used a Completely Randomized Design (CRD) arranged in a factorial manner (2 factors, 4 replications). The first factor tested was the salt sea water concentration (K) which consisted of 4 levels, namely: K0 = no sea water; K1 = ratio of sea water and regular water 25 ml: 75 ml, K2 = ratio of sea water and regular water 50 ml: 50 ml. K3 = ratio of sea water and ordinary water 75 ml: 25 ml. K4 = 100 ml sea water. The second factor is variety (V) which consists of 2 levels, namely: T = Tajuk variety, L = Biru Lancor variety. The results of the research showed that giving sea water to shallot plants had a different effect on vegetative growth for the Biru Lancor variety and the Tajuk variety. The treatment showed that the higher the concentration, the lower the growth. Significant results can be seen in the observed characteristics of plant height at 5, 6, 7 WAP and number of leaves a week at 7 WAP. The use of sea water at a concentration of 50 ml gave an increase in positive results for the Biru Lancor variety for the number of shoots in the 7th week.